F (x) = 2x + 3; find f (–1)" (pronounced as "f-of-x equals 2x plus three; find f-of-negative-one"). In either notation, you do exactly the same thing: you plug –1 in for x, multiply by the 2, and then add in the 3, simplifying to get a final value of +1
200 divided by 5 equals 40.
So therefore, 40 times 5 equals 200.
Answer:
(7m + 63)/3x = k
Step-by-step explanation:
<em>m=3kx/7 - 9</em>
<u><em>add 9 to both sides:</em></u>
m+ 9 = 3kx/7
<u><em>multiply both sides by 7:</em></u>
7(m+9) = 3kx
<u><em>distribute the 7:</em></u>
7m+63 = 3kx
<u><em>divide both sides by 3x:</em></u>
<u>(7m + 63)/3x = k</u>